FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI TEMBAKAU RAKYAT ( Studi Kasus Desa Tegalroso Kecamatan Parakan Kabupaten Temanggung) - Dwiyanti Septi Pertiwi; Fitrie Arianti (Universitas Diponegoro, 2013)
Temanggung regency is the big centre of the traditional tobacco producer in Central Javaand it’s been developing since the ancient time. Almost all area in Temanggung regency producertobacco. One of the producer tobacco at Temanggung regency is Tegalroso village. According tothis fact, this research has purpose to influencing of the production factors tobacco at Tegalrosovillage Parakan sub-district Temanggung regency. Independent variabel that used in this researchAmount of fertilizer, usage of pesticide and manpower usage. Data in this research was usedprimary and secondary. Method of data collecting wa used interview and documentation. DataProcessing done by using of SPSS 11 programme. Method used the Ordinary Least Square (OLS).Result of this research showed that amount of fertilizer, usage of pesticide had positivesignificantly influence of tobacco produce and manpower variable hadn’t significantly influence oftobacco produce. Result of F-test showed that as a simoultaneusly, independent variable inconcomitantly may showed its influence tobacco produce. The R2 value as by 0,816 had means that84,1 percent produce the explainable tobacco by variable wide of farm, amount fertilizer, usage ofpesticide and manpower usage. While the remainder, that is by 18,4 percent was explained byexternal causes.